EFFECT OF AQUEOUS EXTRACT OF PEEL OF CITRUS SINENSIS ON FROG'S HEART - Tripathy, Ratikanta; Pradhan, Manas Ranjan; Lenka, Basudev; Mohanty, Manjushree (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: To evaluate the cardiotonic action of aqueous extract of the peel of Citrus sinensis and also to know the effect in the presence of propranolol, nifedipine, and verapamil. Methods: We studied the cardiotonic effect of citrus peel extracts on isolated frog heart perfusion technique alone and also with a continuous infusion with calcium channel blockers and a beta blocker. The aqueous extract obtained by drying the peel of citrus and then adding the powder form in distilled water. Results: Aqueous extract produced positive ionotropic action on frog heart and its effect antagonized by propranolol but neither by nifedipine nor verapamil. Conclusion: Aqueous extract of peels of C. sinensis has cardiotonic activity and the cardiotonic effect produced by citrus may be due to having beta adrenergic action. Keywords: Digoxin, Cardiac stimulant, Isolated frog's heart, Citrus sinensis.